Cloud computing for mobile applications: outsourcing the deployment of virtual machines (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Application offloading is a software-level technique for enhancing the computecapabilities of smart mobile devices in mobile cloud computing. The use of additionalcomputational resources in the deployment and administration of VM on Smartphone is aproblematic component of such frameworks. Virtual Machine (VM) deployment necessitates theuse of computational resources for VM construction and configuration. The administration ofvirtual machines (VMs) involves computer resource usage, VM lifecycle monitoring, andphysical resource management for VMs on smartphones. The goal of this project is to ensure thatvirtual machine deployment and administration do not necessitate additional processingresources on mobile devices for application offloading. VM deployment, application executiontimes, and the simulation's total execution time are used to evaluate the success of VMdeployment and management in application processing. VM deployment and management,according to the research, need additional resources on the computer host. As a result, deployingvirtual machines on smart mobile devices has become a heavyweight technique for offloadingprocesses.